2008
DOI: 10.2967/jnumed.108.051680
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of β-Cell Mass in Rats Using 18F-FP-(+)-DTBZ: A Potential PET Ligand for Studying Diabetes Mellitus

Abstract: Recent studies on gene expression of b-cell mass (BCM) in the pancreas showed that vesicular monoamine transporter 2 (VMAT2) is highly expressed in the BCM (mainly in the islets of Langerhans). Imaging pancreatic BCM may provide an important tool for understanding the relationship between loss of insulinsecreting b-cells and onset of diabetes mellitus. In this article, 9-fluoropropyl-(1)-dihydrotetrabenazine (FP-(1)-DTBZ), which is a VMAT2 imaging agent, was evaluated as a PET agent for estimating BCM in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 35 publications
(70 reference statements)
3
72
0
Order By: Relevance
“…Ideally, two basic criteria should be met for adequate beta cell imaging [6]: (1) beta cells should retain the tracer 100-to 1,000-fold more than the exocrine cells; and (2) agents that label beta cell surface proteins should do this at high enough concentrations to overcome imaging signals arising from unbound tracer retained in the extracellular and vascular spaces, and from tracer bound to the other tissues surrounding the pancreas. Agents being tested currently for BCM imaging include glibenclamide [6], glucagon-like peptide 1 receptor [7,8], sulfonylurea receptor [6], vesicular monoamine transporter 2 (VMAT2) [9][10][11][12][13] and gangliosides [14]. Unfortunately, the uptake/binding of these agents to beta cells, compared with exocrine pancreas and non-beta cells, is insufficient to allow reliable imaging of the BCM [6,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, two basic criteria should be met for adequate beta cell imaging [6]: (1) beta cells should retain the tracer 100-to 1,000-fold more than the exocrine cells; and (2) agents that label beta cell surface proteins should do this at high enough concentrations to overcome imaging signals arising from unbound tracer retained in the extracellular and vascular spaces, and from tracer bound to the other tissues surrounding the pancreas. Agents being tested currently for BCM imaging include glibenclamide [6], glucagon-like peptide 1 receptor [7,8], sulfonylurea receptor [6], vesicular monoamine transporter 2 (VMAT2) [9][10][11][12][13] and gangliosides [14]. Unfortunately, the uptake/binding of these agents to beta cells, compared with exocrine pancreas and non-beta cells, is insufficient to allow reliable imaging of the BCM [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Promising preliminary data were obtained with 11 C-labelled dihydrotetrabenazine (the PET ligand binding specifically to VMAT2) in streptozotocin (STZ)-induced diabetic Lewis rats [11] and in the BB-DP rat [12], but the data obtained in baboons [15] and in patients with longstanding type 1 diabetes [16] are not conclusive. A recent study using an 18 F-labelled epoxide derivative of tetrabenazine showed good pancreas specificity and significantly reduced uptake in rat liver [9], but it remains unclear whether substituting isotopes will produce better biodistribution results in larger mammals. As a whole, these observations emphasise the need for the identification of new beta cell biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen exponential progress in applying various imaging modalities (MRI, positron emission tomography, optical) for noninvasive detection and monitoring of pancreatic ␤ -cell mass (2)(3)(4)(5)(6). A crucial prerequisite for clinical application of these techniques is the availability of a contrast agent with high affi nity and high specifi city toward ␤ -cell surface markers.…”
mentioning
confidence: 99%
“…The DTBZ analog [ 18 F]FP-DTBZ ( 18 F-AV-133) was prepared with fluorine-18 using precursors supplied by Avid Radiopharmaceuticals (39). Detailed radiochemical synthesis is provided in SI Methods.…”
Section: Methodsmentioning
confidence: 99%